Structure and tectonic evolution of the Fuegian Andes (southernmost South America) in the framework of the Scotia Arc development - Torres Carbonell, Pablo Juan; Dimieri, Luis Vicente; Olivero, Eduardo Bernardo; Bohoyo, Fernando; Galindo Zaldívar, Jesús (Global and Planetary Change)
The major structural and tectonic features of the Fuegian Andes provide an outstanding onshore geological framework that aids in the understanding of the tectonic evolution of the Scotia Arc, mainly known from offshore studies. The orogenic history of the Fuegian Andes (Late Cretaceous-Miocene) is thus compared and integrated with the tectonic history of the Scotia Sea. Late Cretaceous-Paleocene structures in the Fuegian Andes suggest a N-directed contraction consistent with an oroclinal bending of the southernmost South America-Antarctic Peninsula continental bridge. This N-directed contraction in the Fuegian Andes continued during the spreading of the West Scotia Ridge, between 40-50 and 10. Ma ago. The onset of major strike-slip faulting in Tierra del Fuego is considered here to be not older than the late Miocene, consistent with the recent history of the North Scotia Ridge thus forming part of a tectonic regime superposed to the prior contraction in the Fuegian Andes. Fil: Torres Carbonell, Pablo Juan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Dimieri, Luis Vicente. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Geológico del Sur. Universidad Nacional del Sur. Departamento de Geología. Instituto Geológico del Sur; Argentina Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Bohoyo, Fernando. Instituto Geológico y Minero de España; España Fil: Galindo Zaldívar, Jesús. Universidad de Granada; España. Consejo Superior de Investigaciones Científicas; España